Feynmanov pristop h kvantni mehaniki - Krejan, Anže (Matrika, 2024)
Feynman’s path integral formulation of quantum mechanics is a wiser approach to quantum mechanics. It generalizes the concept of classical action to a sum over all possible paths, which can be used to calculate quantum probability amplitudes. First, the derivation of the path integral and its application to the harmonic potential will be presented. This will be followed by a discussion on how the path integral can be used to formulate quasi-classical limits of quantum problems. Finally, the equivalence of this formalism with the Schrödingers picture will be demonstrated through the derivation of the Schrödinger equation from Feynman’s formalism.
Keywords: Feynman’s formalism; Feynmanov formalizem; harmonic potential; harmonski potencial; kvantna mehanika; path integral; popotni integral; quantum mechanics; Schrödinger equation; Schrödingerjeva enačba